Availability of Interventional Oncology in Germany in the Years 2018 and 2019 – Results from a Nationwide Database (DeGIR Registry Data) - Radosa, Christoph Georg; Nadjiri, Jonathan; Mahnken, Andreas H.; Bücker, Arno; Heuser, Lothar J; Morhard, Dominik; Landwehr, Peter; Berlis, Ansgar; Katoh, Marcus; Reimer, Peter; Schachtner, Balthasar; Ingrisch, Michael; Paprottka, Philipp; Hoffmann, Ralf-Thorsten (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Objective Over the past few decades, radiology has established itself in tumor therapy through interventional oncology including innovative and efficient procedures for minimalinvasive treatment of various tumor entities besides the “classic” therapeutic options such as surgery, chemotherapy and radiotherapy.Aim of this study was to evaluate the extent to which interventional oncology can provide nationwide care using the data from the register of the German Society for Interventional Radiology and Minimally Invasive Therapy (DeGIR registry), which records radiological interventions as part of quality assurance.Methods The numbers of interventions of participating clinics, which were recorded as part of module D (oncological procedures including TACE or other tumor-specific embolization, ablation, percutaneous tumor therapy) and identified by the DeGIR registry between 2018 and 2019, were analyzed retrospectively. The collected intervention data were evaluated regarding federal states and 40 smaller regions (administrative districts and former administrative districts).Results In 2018, 11 653 oncological interventions in 187 clinics were recorded by the DeGIR registry. In 2019, the number of participating clinics rose to 216 and the number of oncological interventions increased by 6 % to 12 323. The average number of oncological interventions per clinic decreased slightly from 62.5 (2018) to 57.1 (2019). The DeGIR requirement for being certified as a training center was met by 116 clinics in 2018 including 31 clinics with more than 100 interventions and 129 clinics in 2019 including 36 with more than 100 interventions. Oncological interventions have been performed in each of the 40 regions. An average of 599 interventions per region (standard deviation of 414) was recorded in the period between 2018 and 2019.Conclusion Based on the distribution of the documented oncological interventions at federal state level as well as the district level, the supply of interventional tumor therapy depends on the geographical location. Therefore, the demand of oncological interventions might not be sufficiently covered in some regions.Key Points:Citation FormatZiel In den letzten Jahrzehnten konnte sich die Radiologie durch innovative sowie effiziente onkologische Interventionen neben den „klassischen“ Therapiemöglichkeiten wie Chirurgie, Chemotherapie und Strahlentherapie in der Tumortherapie etablieren. Mithilfe der Daten aus dem Register der deutschen Gesellschaft für interventionelle Radiologie und minimal-invasive Therapie (DeGIR-Register), welches im Rahmen der Qualitätssicherung radiologische Interventionen erfasst, soll evaluiert werden, inwieweit eine deutschlandweite, flächendeckende Versorgung durch interventionell-onkologische Verfahren zur Behandlung von Malignomen erreicht wird.Material und Methoden Retrospektiv wurden alle Untersuchungszahlen der teilnehmenden Kliniken, welche im Rahmen von Interventionen des Moduls D (onkologische Verfahren inkl. TACE oder andere tumorspezifische Embolisationen, Ablationen, perkutane Tumortherapien) mittels DeGIR-Register zwischen 2018 und 2019 erfasst wurden, ausgewertet. Die erhobenen Interventionszahlen wurden nach Bundesländern sowie Regierungsbezirken aufgeschlüsselt.Ergebnisse Im Jahr 2018 wurden in 187 Kliniken 11 653 onkologische Interventionen im DeGIR-Register erfasst. 2019 stieg die Anzahl der teilnehmenden Kliniken auf 216 sowie die Anzahl der dokumentierten onkologischen Interventionen bei einem Zuwachs von 6 % auf 12 323. Bei der durchschnittlichen Anzahl der dokumentierten onkologischen Interventionen pro Klinik kam es zu einem leichten Rückgang von 62,3 (2018) auf 57,1 (2019). Als DeGIR-Ausbildungszentrum wurden 2018 116 Kliniken (31 mit mehr als 100 Interventionen) und 2019 129 Kliniken (36 mit mehr als 100 Interventionen) geführt. In allen aufgeschlüsselten Regionen wurden onkologische Interventionen dokumentiert. Insgesamt wurden durchschnittlich 599 Interventionen (Standardabweichung 414) im Zeitraum von 2018 bis 2019 pro Region erfasst.Schlussfolgerung Die Verteilung der dokumentierten onkologischen Interventionen auf Bundeslandebene sowie innerhalb der aufgeschlüsselten Regionen zeigt eine geografisch unterschiedlich ausgeprägte Versorgung mit interventionellen Tumortherapien, sodass in einzelnen Regionen der Bedarf an interventionell-onkologischen Verfahren noch nicht ausreichend gedeckt sein könnte.Kernaussagen:Zitierweise
Keywords: DeGIR registry data; interventional radiology; interventional oncology; quality assurance